Business Strategy for the implementation of Mobile JKN Faskes Application - Johan Riawan; Satya Aditya Wibowo (Universitas Mercu Buana Yogyakarta, 2022)
BPJS Kesehatan (BPJSK) to improve the quality of its services presents the Mobile JKN Faskes (MJF) application, a teleconsultation Application used for a doctor in National Health Insurance Progam (JKN). There is a significant increase in the prevalence of comparable applications under pandemic conditions, which may provide a challenge to the role of MJF. This research was developed to Propose a Business Strategy to ensure the adoption of the MJF by Primary Health Care amid the rise of similar teleconsultation applications. The aspects that influence application acceptance will be researched in terms of developing a suitable strategy. Through an examination of the MJF features that need to be developed, An Application, which refers to customer orientation becomes part of the research. Research reveals that the Social Influence of the teleconsultation system is the most influential factor of application utilization, and various MJF features need improvement. Acceptance of the MJF was studied with the Unified Theory Of Acceptance And Use Of Technology (UTAUT) model as part of customer analysis, Strategy formulation was conducted after internal and external analysis